Filmen, Forschen, Annotieren Handbuch Research Video - Lösel, Gunter; Zimper, Martin (De Gruyter, 2021)
The handbook Research Video is the introduction to a new kind of software and publication based on annotated videos. Practitioners and researchers who work with motion data, such as those from the fields of performative art, film, behavioral research or sports science, are supported in their work process and are given the opportunity to feed in content that a printed book cannot convey.